International Measures on the Legal Issues of Human Rights Protection from a Coup d'état - Yordying, Wanchanok; Noichim, Chukeat (Nitipat NIDA Law Journal, 2023)
The research study found that in the past, coups were only about seizing state power or changing leaders from the government. The governance structure and socio-economic situation remain unchanged and may even worsen. Currently, a coup and/or any support for a coup is considered a gross Violation of Human Rights. In addition to violating human rights and freedoms, it also reflects a decline in national quality and standards. The purpose of this study is to find guidelines and measures for irresponsible coup groups that violate human rights. When each coup was successful thereafter the individuals and/or groups of people who executes those coups will use both domestic and international law to apply it for their own benefit. For example, applying for a domestic amnesty for oneself and inheriting one's power through an election symbol (unfair) to obtaining certification from governments of various countries, which have created the conditions for certifying democratic governments only after elections. Therefore, it is considered a vicious circle of serious human rights violations all along and never ends. Therefore, in order to bring the coup d'etat to responsibility for what has been done and/or prevent the occurrence of another coup d'etat, it is appropriate to (1) develop measures to prove that the new government must be a democratically elected government that respects the rule of law to protect human Rights and (2) amendment the act of “A coup and/or support for a coup is a gross Violation of Human Rights " in the International human rights instruments.